Prodrug Strategies in the CNS Drugs: Small Modification Makes Big Improvements - Kang, Ting; Miao, Zhuang; Liu, Siyu; Ke, Bowen (Current Topics in Medicinal Chemistry, 2021)
Prodrug design is an effective method proven to improve the drug-like properties of a molecule, and it has been widely used in the drug development of various diseases. Due to the complexity of the central nervous system (CNS), the development of CNS drugs has high requirements related to the pharmaceutical, pharmacokinetic, and pharmacodynamic properties of the molecules. Prodrug design has now been widely and successfully applied to improve these properties. We conducted a mini-review to promote the use of the prodrug strategies in CNS drug development. To facilitate the description, we chose drug indications as a clue, then presented and discussed some representative CNS prodrugs. Finally, a brief summary and outlook about this area were presented.
Keywords: Prodrug strategies